2022
DOI: 10.54766/rberu.v15i3.763
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades Regionais e Infraestrutura: Uma Análise de Curto e Longo Prazo da UTE Porto de Sergipe

Abstract: Este trabalho objetiva avaliar os impactos regionais e setoriais de curto e longo-prazo da construção e operação da Usina Termelétrica Porto de Sergipe. Utiliza-se um modelo dinâmico e inter-regional de Equilíbrio Geral Computável, calibrado para 28 regiões e 51 setores. Em termos metodológicos, a inovação deste trabalho consiste em desagregar Sergipe em duas regiões no modelo: Região Metropolitana de Aracaju (RMA) e Resto de Sergipe (RS). Os resultados apontam para um relevante impacto na RMA, com baixo vazam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In an analysis for the state of Sergipe using the Location Quotient, Vieira et al. (2020) found that the Public Utility Industrial Services (SIUP) the most specialized industry in the state in 2002, 2010 and 2017. The municipality of Canindé de São Francisco is where the power plant is located.…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis for the state of Sergipe using the Location Quotient, Vieira et al. (2020) found that the Public Utility Industrial Services (SIUP) the most specialized industry in the state in 2002, 2010 and 2017. The municipality of Canindé de São Francisco is where the power plant is located.…”
Section: Resultsmentioning
confidence: 99%